STUDIES ON INTERFERENCE AMONG TREES IN A PLANTATION OF ALTINGIA EXCELSA - KAN-ICHI SAKAI (SEAMEO BIOTROP, 1987)
A study was made with the use of a 50-year old Altingia excelsa Noronha plantation with 260 standing trees for separating components of density and intraspecific competition. A component of density effect causes overall decrease in growth while that of competition results in a contrasting effect in growth between any pair of neighboring trees. To detect this density effect, it is most appropriate to use an area of ca. 100 m2 irrespective of the experimental area, e.g. circular or quadratic. Competition effect cannot be detected when two individuals are apart more than two meters. An application of the density and competitive ability to tree breeding is briefly mentioned.